Does wealth inequality reduce the gains from trade? - Caselli, M (CSAE (University of Oxford), 2008)
Panel data on 54 developing countries between 1960 and 2000 are used to investigate how the impact of opening to trade on economic growth is affected by wealth inequality. The results suggest (a) that opening to trade tends to accelerate growth but (b) that the addition to growth depends inversely on the level of wealth inequality prior to opening. These findings confirm the general importance for rapid growth in developing countries of reducing inequalities of opportunity.